Effects of Incorporation of Additives in the Mechanical Properties of Films of Linear Low-Density Polyethylene - Delgado, Emilio; Aperador Chaparro, William; Carrillo León, Juan (TECCIENCIA, 2017)
In this investigation the effect of the incorporation of additives in the mechanical properties of LLDPE films, made to be used as greenhouse covers, was analyzed. All films were fabricated by the method of extrusion blow. Two types of formulations are raised in order to determine the influence of the concentration of one additive and identify the existence of some synerg y by combining active ingredients in the formulations. Modulus of elasticity, yield stress and tear resistance of the films were evaluated. The results indicate that variation in the concentration of an additive in the mixture does not generate significant changes in the physical-mechanical properties of the films. However, the incorporation of the UV light absorber and Smartlight photoselector in formulations favors their mechanical properties. Compared with the reference film, an increase higher than 200% in modulus of elasticity and yield stress of the films was determined.